2021
DOI: 10.1111/jrh.12572
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating disparities in access to obstetric services for American Indian women across Montana

Abstract: Purpose Pregnant women across the rural United States have increasingly limited access to obstetric care, especially specialty care for high‐risk women and infants. Limited research focuses on access for rural American Indian/Alaskan Native (AIAN) women, a population warranting attention given persistent inequalities in birth outcomes. Methods Using Montana birth certificate data (2014–2018), we examined variation in travel time to give birth and access to different levels of obstetric care (i.e., the proporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Important underlying reasons for such gaps included lack of transport, cost, and low levels of trust and confidence in the child's GP. A similar pattern is found internationally, with lower utilisation of healthcare services among ethnic minority groups [6][7][8], and particularly for indigenous ethnic groups [9]. In the US, children from racial minority and marginalised communities were found to have poorer health status and disrupted access to care [10].…”
Section: Introductionsupporting
confidence: 57%
“…Important underlying reasons for such gaps included lack of transport, cost, and low levels of trust and confidence in the child's GP. A similar pattern is found internationally, with lower utilisation of healthcare services among ethnic minority groups [6][7][8], and particularly for indigenous ethnic groups [9]. In the US, children from racial minority and marginalised communities were found to have poorer health status and disrupted access to care [10].…”
Section: Introductionsupporting
confidence: 57%
“…Travel burdens in rural America pose a significant challenge to rural health care access 17,42,43 . Rural communities, especially those in frontier and/or remote areas, face persistent barriers to maintaining local maternity units, 3–6,44 challenging the ongoing efforts to ensure access to maternity care.…”
Section: Discussionmentioning
confidence: 99%
“…Travel burdens in rural America pose a significant challenge to rural health care access. 17,42,43 Rural communities, especially those in frontier and/or remote areas, face persistent barriers to maintaining local maternity units, [3][4][5][6]44 challenging the ongoing efforts to ensure access to maternity care. Several statewide studies have found that travel burdens to maternity care were associated with lower rates of prenatal care uptake, and higher rates of preterm births, low birthweights, and neonatal mortality.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11] Recent findings suggest a lack of access and disparities in geographic access will persist unless facility-level infrastructure is expanded. 12 However, geographic access to obstetric care is measured in several ways, which causes uncertainty about how to optimally invest in infrastructure to expand access. One common measure of access in the academic literature and news media is the maternity care desert, as defined by the March of Dimes.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 However, the maternity care deserts access measure does not necessarily reflect distance to care because counties differ in size and some pregnant women within a county may live close to an obstetric facility in a neighboring county. Other studies have measured geographic access as driving time to the nearest facility offering obstetric services at different levels of care 12,18 and distance to the nearest facility offering critical care obstetric (CCO) services 19,20 as key measures for quantifying potential access.…”
Section: Introductionmentioning
confidence: 99%